COMMUNITIES OF THE LIGHTED ZONE OF HYPOGEAN MONASTIC CELLS OF THE ROCK MONASTERY "DORMITION OF GOD'S MOTHER", THE RESERVE OLD ORHEY - Svetlana E. Mazina; Anna V. Popkova (Юг России: экология, развитие)
Abstract. Aim. An analysis of species composition (phototrophic organisms and micromycetes) of epibioses communities of entrance area of monastic cells of the historical and archaeological complex of Old Orhei. Comparison of species composition of epibioses communities on the surface areas and in the cells. Comparison of phototrophic species composition of abovementioned communities with similar communities of the cult chalk caves of the Voronezh region and limestone grottoes of Podolsky Tovtry. Objects. The object of the investigation was the entrance area of the monastic cells of the rocky monastery "Dormition of God’s Mother", the reserve of Old Orhei (Moldova). Methods. Phototrophic species composition was determined by the methods of microscopy and inoculation in the culture medium. Mosses and lichens from epibioses communities were studied by traditional botanical methods. Micromycetes were studied by isolation methods on the Chapec-Dox selective medium. The abundance and occurrence of species in communities was determined. Results. Biodiversity of epibioses communities of hypogean habitats was revealed. It is shown that the species diversity on the surface is similar to the species composition in caves. The dominant species in the underground and surface epibioses communities were determined. The similarity of the species composition of the flora with caves of the Voronezh region and Ukraine was not revealed. Conclusions. Cyanobacteria predominate in the flora structure of the monastic cells of the rocky monastery "Dormition of God’s Mother". Micromycetes of epibioses communities are represented by widespread soil species. The species composition of cells is similar to the species composition on the surface. It can be assumed that the species composition of hypogean habitats is determined by a complex of conditions, among which the most important is the illumination, temperature and humidity, substrate quality and species composition on the surface.